To solve the equation \( 12(1.2x + 4.65) = 15(x + 3.5) \), we start by distributing both sides.
Step 1: Distribute on both sides.
Left side: \[ 12(1.2x) + 12(4.65) = 14.4x + 55.8 \]
Right side: \[ 15(x) + 15(3.5) = 15x + 52.5 \]
Now the equation looks like: \[ 14.4x + 55.8 = 15x + 52.5 \]
Step 2: Move all terms involving \( x \) to one side and constant terms to the other side.
Subtract \( 14.4x \) from both sides: \[ 55.8 = 15x - 14.4x + 52.5 \]
This simplifies to: \[ 55.8 = 0.6x + 52.5 \]
Subtract \( 52.5 \) from both sides: \[ 55.8 - 52.5 = 0.6x \]
This simplifies to: \[ 3.3 = 0.6x \]
Step 3: Solve for \( x \).
To isolate \( x \), divide both sides by \( 0.6 \): \[ x = \frac{3.3}{0.6} \]
Calculating this gives: \[ x = 5.5 \]
So the solution to the equation \( 12(1.2x + 4.65) = 15(x + 3.5) \) is: \[ \boxed{5.5} \]